Réponses

Meilleure réponse !
2014-05-14T22:37:34+02:00
Bonsoir,

A= ( x - 3 )² + ( x - 3 ) ( 1 - 2x )

1-Developper A

A= ( x - 3 )^2 + ( x - 3 ) ( 1 - 2x )\\\\A= ( x^2-6x+9)+ (x-2x^2-3+6x)\\\\A=  x^2-6x+9+ x-2x^2-3+6x\\\\\boxed{A= -x^2+x+6}


2-Prouvez que l'expression factoriseé de A est : ( x - 3 ) ( -x - 2 )

A= ( x - 3 )^2 + ( x - 3 ) ( 1 - 2x )\\\\A= ( x - 3 )(x-3) + ( x - 3 ) ( 1 - 2x )\\\\A= ( x - 3 ) [(x-3) + ( 1 - 2x )]\\\\A= ( x - 3 ) (x-3 +  1 - 2x )\\\\\boxed{A= ( x - 3 ) (-x-2)}

3-Résoudre l'équation A=0

A=0\\\\( x - 3 ) (-x-2)=0\\\\ x - 3=0\ \ ou\ \ -x-2=0\\\\ x =3\ \ ou\ \ -x=2\\\\ x =3\ \ ou\ \ x=-2\\\\\boxed{S=\{3;-2\}}